Homeschooling in Beijing, China : Learning from the experiences of parents - Zhao, Junya (Kulliyyah of Education, International Islamic University Malaysia, 2015)
Homeschooling, as a new form of education, is currently emerging in China. The objectives of the study are to investigate the motives of parental homeschooling, and their homeschooling experiences in Beijing, China. In the current study, phenomenological research method has been adopted. Four homeschooling parents and four homeschooling children aged between seven to fifteen years old were interviewed face-to-face in the natural settings. They were recruited through snowball sampling. They were purposely chosen for their common demographical characteristics, socio-economic status, and educational level. Results from the findings revealed that the parental motivation of homeschooling is mainly related to parents' concerns and dissatisfaction towards the current educational systems in China. In conducting homeschooling, various practices shared by parents are reading, religious education, using of different curriculums, music/audio education and other educational resources. The issues of socialization in homeschooling were identified in the study. The findings also revealed the problems and challenges faced by the homeschooling families, internally and externally. As the implications of the study, some recommendations were outlined as the continuance for the future research in this area, and for the betterment of homeschooling in China, respectively from the perspectives of parents, teachers, educators, educational organizations and local government. Homeschooling, as a viable alternative to traditional education, opens another door for the future generation in China.